Permasalahan Gizi Lanjut Usia - Nuhaliza, Nuhaliza; Ambo Hamsah, Idawati; Arfan, Farmin (Mando Care Jurnal, 2021)
Based on the ministry of Health or the ministry of health (2019), indonesia is starting to enter a period of anging populaation, where there is an increase in life expectancy followed by an increase in the number of elderly people. In indonesia , there is an increase in the number of elderly people from 18 milion people ( 7.56%) in 2010, to 25.9 milion people (9.7%) in 2019, and can be expected to cantinue to increase where in 2035 to 48.2 milion people (15,77%). This studay aims to add insight and deepen knowledge, especially in the field , of elderly nutrition and can examine the extent to which the theory excamine the extent to which the theory obatained and its application in people’s lives in sidodadi village, the method in this study is an observational analytic study using a cross sectional approach. Cross sectional appreach is a type of research that emphasizes the measurement time or data observstion at a time. (Ringer, 2015) based on the results of the study, it can be seen that the number of respondents with female gender is 13 people (56.5%) and the number of men is less than 10 people (43.4%).